Let's assume two variables x and y which represent the local and international calls respectively.
x + y = 852 = total number of minutes which were consumed by the company (equation 1)
0.06*x+ 0.15 y =69.84 = total price which was charged for the phone calls (Equation 2)
from equation 1:-
x=852 -y (sub in equation 2)
0.06 (852 - y) + 0.15 y =69.84
51.12 -0.06 y +0.15 y =69.84 (subtracting both sides by 51.12)
0.09 y =18.74
y= 208 minutes = international minutes (sub in 1)
208+x=852 (By subtracting both sides by 208)
x = 852-208 = 644 minutes = local minutes
Answer:
149.28 sq. inches
137.5 cubic inches.
Step-by-step explanation:
The cylindrical container has length or height (h) 7 inches and has a diameter of 5 inches i.e. radius (r) 2.5 inches.
Now, total surface area of the container =
=
= 39.28 + 110
= 149.28 sq. inches (Answer)
Again the volume of the container will be
=
= 137.5 cubic inches. (Answer)
Use a half-angle identity to find the exact value of sin pi/8
Answer:
8/45
Step-by-step explanation:
Define x to be the value of your fraction:
![x=0.1\overline{7}\\\\10x=1.7\overline{7}\qquad\text{multiply by 10}\\\\10x-x=1.7\overline{7}-0.1\overline{7}=1.6\\\\x=\dfrac{1.6}{9}=\dfrac{8}{45}\qquad\text{divide by 9; put in lowest terms}](https://tex.z-dn.net/?f=x%3D0.1%5Coverline%7B7%7D%5C%5C%5C%5C10x%3D1.7%5Coverline%7B7%7D%5Cqquad%5Ctext%7Bmultiply%20by%2010%7D%5C%5C%5C%5C10x-x%3D1.7%5Coverline%7B7%7D-0.1%5Coverline%7B7%7D%3D1.6%5C%5C%5C%5Cx%3D%5Cdfrac%7B1.6%7D%7B9%7D%3D%5Cdfrac%7B8%7D%7B45%7D%5Cqquad%5Ctext%7Bdivide%20by%209%3B%20put%20in%20lowest%20terms%7D)
____
When in doubt, you can use your calculator to see which fraction gives you 0.1777777778.
_____
We multiplied by 10^1 above, because there is 1 repeating digit. The power of 10 we use matches the number of repeating digits.
A. Factor the numerator as a difference of squares:
![\displaystyle\lim_{x\to9}\frac{x-9}{\sqrt x-3}=\lim_{x\to9}\frac{(\sqrt x-3)(\sqrt x+3)}{\sqrt x-3}=\lim_{x\to9}(\sqrt x+3)=6](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Clim_%7Bx%5Cto9%7D%5Cfrac%7Bx-9%7D%7B%5Csqrt%20x-3%7D%3D%5Clim_%7Bx%5Cto9%7D%5Cfrac%7B%28%5Csqrt%20x-3%29%28%5Csqrt%20x%2B3%29%7D%7B%5Csqrt%20x-3%7D%3D%5Clim_%7Bx%5Cto9%7D%28%5Csqrt%20x%2B3%29%3D6)
c. As
![x\to\infty](https://tex.z-dn.net/?f=x%5Cto%5Cinfty)
, the contribution of the terms of degree less than 2 becomes negligible, which means we can write
![\displaystyle\lim_{x\to\infty}\frac{4x^2-4x-8}{x^2-9}=\lim_{x\to\infty}\frac{4x^2}{x^2}=\lim_{x\to\infty}4=4](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Clim_%7Bx%5Cto%5Cinfty%7D%5Cfrac%7B4x%5E2-4x-8%7D%7Bx%5E2-9%7D%3D%5Clim_%7Bx%5Cto%5Cinfty%7D%5Cfrac%7B4x%5E2%7D%7Bx%5E2%7D%3D%5Clim_%7Bx%5Cto%5Cinfty%7D4%3D4)
e. Let's first rewrite the root terms with rational exponents:
![\displaystyle\lim_{x\to1}\frac{\sqrt[3]x-x}{\sqrt x-x}=\lim_{x\to1}\frac{x^{1/3}-x}{x^{1/2}-x}](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Clim_%7Bx%5Cto1%7D%5Cfrac%7B%5Csqrt%5B3%5Dx-x%7D%7B%5Csqrt%20x-x%7D%3D%5Clim_%7Bx%5Cto1%7D%5Cfrac%7Bx%5E%7B1%2F3%7D-x%7D%7Bx%5E%7B1%2F2%7D-x%7D)
Next we rationalize the numerator and denominator. We do so by recalling
![(a-b)(a+b)=a^2-b^2](https://tex.z-dn.net/?f=%28a-b%29%28a%2Bb%29%3Da%5E2-b%5E2)
![(a-b)(a^2+ab+b^2)=a^3-b^3](https://tex.z-dn.net/?f=%28a-b%29%28a%5E2%2Bab%2Bb%5E2%29%3Da%5E3-b%5E3)
In particular,
![(x^{1/3}-x)(x^{2/3}+x^{4/3}+x^2)=x-x^3](https://tex.z-dn.net/?f=%28x%5E%7B1%2F3%7D-x%29%28x%5E%7B2%2F3%7D%2Bx%5E%7B4%2F3%7D%2Bx%5E2%29%3Dx-x%5E3)
![(x^{1/2}-x)(x^{1/2}+x)=x-x^2](https://tex.z-dn.net/?f=%28x%5E%7B1%2F2%7D-x%29%28x%5E%7B1%2F2%7D%2Bx%29%3Dx-x%5E2)
so we have
![\displaystyle\lim_{x\to1}\frac{x^{1/3}-x}{x^{1/2}-x}\cdot\frac{x^{2/3}+x^{4/3}+x^2}{x^{2/3}+x^{4/3}+x^2}\cdot\frac{x^{1/2}+x}{x^{1/2}+x}=\lim_{x\to1}\frac{x-x^3}{x-x^2}\cdot\frac{x^{1/2}+x}{x^{2/3}+x^{4/3}+x^2}](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Clim_%7Bx%5Cto1%7D%5Cfrac%7Bx%5E%7B1%2F3%7D-x%7D%7Bx%5E%7B1%2F2%7D-x%7D%5Ccdot%5Cfrac%7Bx%5E%7B2%2F3%7D%2Bx%5E%7B4%2F3%7D%2Bx%5E2%7D%7Bx%5E%7B2%2F3%7D%2Bx%5E%7B4%2F3%7D%2Bx%5E2%7D%5Ccdot%5Cfrac%7Bx%5E%7B1%2F2%7D%2Bx%7D%7Bx%5E%7B1%2F2%7D%2Bx%7D%3D%5Clim_%7Bx%5Cto1%7D%5Cfrac%7Bx-x%5E3%7D%7Bx-x%5E2%7D%5Ccdot%5Cfrac%7Bx%5E%7B1%2F2%7D%2Bx%7D%7Bx%5E%7B2%2F3%7D%2Bx%5E%7B4%2F3%7D%2Bx%5E2%7D)
For
![x\neq0](https://tex.z-dn.net/?f=x%5Cneq0)
and
![x\neq1](https://tex.z-dn.net/?f=x%5Cneq1)
, we can simplify the first term:
![\dfrac{x-x^3}{x-x^2}=\dfrac{x(1-x^2)}{x(1-x)}=\dfrac{x(1-x)(1+x)}{x(1-x)}=1+x](https://tex.z-dn.net/?f=%5Cdfrac%7Bx-x%5E3%7D%7Bx-x%5E2%7D%3D%5Cdfrac%7Bx%281-x%5E2%29%7D%7Bx%281-x%29%7D%3D%5Cdfrac%7Bx%281-x%29%281%2Bx%29%7D%7Bx%281-x%29%7D%3D1%2Bx)
So our limit becomes